Comparative Analysis of Labour Market Demand for the Economics Graduates in Romania and Poland - Luminița NICOLESCU; Lavinia Cornelia BUTUM (Revista de Management Comparat International)
The changes recorded in the business, professional and cultural environment at the global level explain the phenomenon of internationalization of demand for skills and competencies necessary for the labour market. Given the increasing influence of companies operating on international markets, in this article, it is proposed to identify the demand for skills and competencies required for the largest labour markets in Eastern Europe, respectively Romania and Poland. Starting from previous studies that highlighted the wide typology and the classification of skills and abilities based on the theoretical concepts related to global competencies formation, the present work analyzes the use of global competences in job requirements for HE Ecomomics’ graduates in Romania and Poland. Thus, the paper proposes an analysis at employers’ level in order to identify the demand for global competencies necessary for employment for HE Economics graduates. The study will use a qualitative research method based on content analysis of job announcements for HE Ecomomics’ graduates. The results are obtained from the uses of the contingency matrix for employment adverts from Romania and Poland that select HE Ecomomics’ graduates. The results identified a wide range of similarities but also a few differences in terms of demand of skills and abilities for HE Economics’ graduates from Romania and Poland.